2021
DOI: 10.1108/ijppm-12-2020-0678
|View full text |Cite
|
Sign up to set email alerts
|

Developing IT-enabled performance monitoring system for green logistics: a case study

Abstract: PurposeLogistics companies are compelled to improve their efficiency and the environmental performance by introducing the green concept in their operations. The main purpose of the paper is to have continuous monitoring and tracking of logistics operations to enhance the green performance.Design/methodology/approachThis research uses a case study approach. It illustrates a monitoring system to digitize the logistics activities by sending real-time GPS data to the server and capture the surrounding pictures wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
0
16
0
4
Order By: Relevance
“…Rather many studies have focused on operationa performance (e.g. Martens et al, 2022); Chhabra et al, 2022). Based on this, it is likely that IoT may in time, be considered as one of the suite of tools and techniques such as TQM, VMI, CRM, etc.…”
Section: The Importance Of Different Indicatorsmentioning
confidence: 99%
“…Rather many studies have focused on operationa performance (e.g. Martens et al, 2022); Chhabra et al, 2022). Based on this, it is likely that IoT may in time, be considered as one of the suite of tools and techniques such as TQM, VMI, CRM, etc.…”
Section: The Importance Of Different Indicatorsmentioning
confidence: 99%
“…Considering the activities developed along the value chain of a company, the importance of the activities that make up the logistic systems to achieve good results in terms of sustainability is highlighted (Chhabra et al. , 2022; Jozef et al.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the implementation of digital technologies are becoming increasingly relevant for corporate and performance management (Oliver, 2018;Marrone and Hazelton, 2019;Wang et al, 2020aWang et al, , 2020bChatterjee et al, 2021;Jun et al, 2021), and especially ETs have demonstrated in the last years to be particularly supportive in fostering these issues in health care (Spanò and Ginesti, 2021), transportation (Chhabra et al, 2021), manufacturing (Rezaei et al, 2017) and so on.…”
Section: Introductionmentioning
confidence: 99%